Furfural: hemicellulose/xylosederived biochemical - Mamman, Ajit Singh; Lee, Jong-Min; Kim, Yeong-Cheol; Hwang, In Taek; Park, No-Joong; Hwang, Young Kyu; Chang, Jong-San; Hwang, Jin-Soo (Biofuels Bioproducts & Biorefining-Biofpr, 2008)
Hemicellulose, the second, most common polysaccharide in nature constitutes approximately 20-35% of lignocellulosic biomass. Effective utilization of biomass, hitherto underutilized, is gaining tremendous importance for the production of energy, fuels, and chemicals. Amongst the vast array of chemicals derived from lignocellulosics, furfural is the key chemical that finds wide applications in oil refining, plastics, pharmaceutical and agrochemical industries. There is no synthetic route for the production of furfural. A few conventional technologies currently in practice for its separation and subsequent isolation are appropriately reviewed. Major disadvantages associated with processes currently used for the production of furfural based on acid-catalyzed hydrolysis have been discussed. A need to develop a process which is devoid of all the shortcomings associated with conventional process is emphasized. Several important aspects of chemistry underlying the acid hydrolysis of xylose are discussed. The importance of myriad pre-treatment steps involved to surmount the physical and chemical barriers and to liberate xylose from the confines of acid-resistant layer of lignin has been emphasized. New developments in the production of furfural from cyclodehydration of xylose using solid acid catalysts in the recent past have been reviewed appropriately in present communication. Finally, the production of furfural and furfuryl alcohol, their domestic market and export in China deserve some coverage and therefore have appropriately been discussed as well. (c) 2008 Society of Chemical Industry and John Wiley & Sons, Ltd
Keywords: acid hydrolysis; cyclodehydration; furfural; Hemicellulose; pre-treatment of lignocellulosics; Xylose

Utilization of sugarcane bagasse cellulose for producing cellulose acetates: novel use of residual hemicellulose as plasticizer - Shaikh, Hamid M.; Pandare, Kiran V.; Nair, Greeshma; Varma, Anjanikumar (Carbohydrate Polymers, 2009)
Sugarcane bagasse was fractionated to cellulose, hemicellulose and lignin by a proprietary steam explosion process, followed by downstream purifications, developed in our laboratory. The fractionated cellulose contained similar to 94% cellulose, about similar to 5% hemicellulose, traces of lignin (similar to 0.2%), and similar to 1% ash. The cellulose was acetylated under heterogeneous conditions to obtain cellulose acetates. These were extensively characterized using FTIR, TGA, DSC, GPC, HPIC, WAXRD, and viscometry. The novel feature of this study was the utilization of the hemicellulose content (5%) of bagasse cellulose as an internal plasticizer. Through kinetic experimentation, we have demonstrated that the residual hemicellulose need not be considered as an impurity; rather it can be used in acetylated form as a plasticizer as well as a biodegradable additive for cellulose acetates made from slightly impure cellulose produced from non-wood origin. Our results therefore show how lignocellulosic agricultural wastes can be utilized to produce high value plastics. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Bagasse cellulose; Cellulose acetate; Hemicellulose; Plasticizer; Sugarcane bagasse; Xylan acetate

Biocatalytic approach for the utilization of hemicellulose for ethanol production from agricultural residue using thermostable xylanase and thermotolerant yeast - Menon, Vishnu; Prakash, Gyan; Prabhune, Asmita; Rao, Mala (Bioresource Technology, 2010)
A hydrolysis of 62% and 50% for OSX (Oat spelt xylan) and WBH (Wheat bran hemicellulose) were obtained in 36 h and 48 h using Accellerase(TM) 1000 at 50 degrees C wherein thermostable xylanase from alkalothermophilic Thermomonospora sp. yielded 67% (OSX) in 3 h and 58% (WBH) in 24 h at 60 degrees C, favouring a reduction in process time and enzyme dosage. The rate of hydrolysis with thermostable xylanase was increased by 20% with the addition of nonionic surfactant tween 80 or biosurfactant sophorolipid. The simultaneous saccharification and fermentation (SSF) of OSX and WBH using thermostable xylanase and D. hansenii in batch cultures produced 9.1 g/L and 9.5 g/L of ethanol, respectively and had a shorter overall process time than the separate hydrolysis and fermentation (SHF). The immobilized yeast cells in Ca-alginate matrix produced ethanol with a yield of 0.46 g/g from hemicellulosic hydrolysates and were reused six times with 100% fermentation efficiency. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biosurfactant; Ethanol; Hemicellulose; Thermostable xylanase; Thermotolerant yeast

Efficient, stable, and reusable silicoaluminophosphate for the one-pot production of furfural from hemicellulose - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (ACS Catalysis, 2013)
Development of stable, reusable, and water tolerant solid acid catalysts in the conversion of polysaccharides to give value-added chemicals is vital because catalysts are prone to undergo morphological changes during the reactions With the anticipation that silicoaluminophosphate (SAPO) catalysts will have higher hydrothermal stability, those were synthesized, characterized, and employed in a one-pot conversion of hemicellulose. SAPO-44 catalyst at 170 degrees C within 8 h could give 63% furfural yield with 88% mass balance and showed similar activity up to at least 8 catalytic cycles. The morphological studies revealed that SAPO catalysts having hydrophilic characteristics are stable under reaction conditions.
Keywords: furfural; Hemicellulose; hydrophilicity; SAPO; water-tolerant catalyst; zeolite

Value addition to lignocellulosics and biomass-derived sugars: an insight into solid acid-based catalytic methods - Bhaumik, Prasenjit; Deepa, Ayillath K.; Kane, Tanushree; Dhepe, Paresh Laxmikant (Journal of Chemical Sciences, 2014)
For the synthesis of important platform chemicals such as sugars (xylose and arabinose) and furans (furfural and 5-hydroxymethylfurfural (HMF)) from carbohydrates (hemicellulose and fructose) solid acid catalysts are employed. Similarly, over solid acid catalysts, conversion of lignin into aromatic monomers is performed. It is observed that in the dehydration of fructose, because of higher hydrothermal stability, silicoaluminophosphate (SAPO) catalysts give better activity (78% HMF yield) compared with other solid acid catalysts (<63% HMF yield) at 175 degrees C. Particularly, SAPO-44 catalyst can be reused at least 5 times with marginal decrease in the activity. Zeolite, BUSY (Si/Al = 15) is active in the conversion of isolated (pure) hemicellulose to produce 41% C-5 sugars in water. The catalyst is also active in the selective conversion of hemicellulose from bagasse to yield 59% C-5 sugars. It is possible to obtain high yields of furfural (54%) directly from bagasse if instead of water, Water+toluene solvent system is used. Depolymerization of lignin using HUSY catalyst produced aromatic monomers with 60% yield at 250 degrees C. A detailed catalyst characterization study is performed to understand the correlation between catalyst activity and morphology. To understand the effect of impurities present in the substrate over solid acid catalysts, metal-exchange study is carried out.
21st National Symposium on Catalysis (CATSYMP), CSIR Indian Inst Chem Technol, Hyderabad, INDIA, FEB 11-13, 2013
Keywords: aromatic monomers; Biomass; furans; Hemicellulose; lignin; solid acid catalyst

Effects of careful designing of SAPO-44 catalysts on the efficient synthesis of furfural - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (Catalysis Today, 2015)
Considering the growing importance of furfural, it is necessary to develop a robust solid acid catalyst for the conversion of xylan (hemicelluloses) into furfural in a one-pot method. In this study, the effects of various components (Si, Al and P) and crystallization time on the preparation of acidic materials and their properties are extensively described. It is seen that with the increase in crystallization time (0, 48, 96, 176 h) during the synthesis of silicoaluminophosphate (SAPO-44), materials morphology changes from amorphous to AFI to CHA and the best activity for furfural synthesis (82%) from xylan was observed with SAPO-44 catalyst aged for 176 h. Since, acidity in the SAPO-44 is guided by the incorporation of Si in the ALPO framework, study on Si molar concentration (0.8, 1.0, 1.2, 1.4 and 1.6) in SAPO-44 was carried out and it was observed that SAPO-44 having 1.0 mole of Si content is the best catalyst for the xylan/xylose conversion to furfural. Catalyst structure-activity correlation is thoroughly defined with the help of several physico-chemical properties. (C) 2014 Elsevier B.V. All rights reserved.
7th Tokyo Conference on Advanced Catalytic Science and Technology (TOCAT), Kyoto, JAPAN, JUN 01-06, 2014
Keywords: Biomass; furfural; Hemicellulose; SAPO-44; Xylose